Analysis of Information on The Development of Community Media Based on Local Wisdom - Yuliasari, Ika (Asian Journal of Social and Humanities, 2025)
The development of information and communication technology supports communication culture and civilization. The use of new media by people in cities and villages is a communication phenomenon in the digital era. The convergence of community media with digital media platforms is a collaboration of technology and development information content This article was written based on the results of research on development information content in community radio media RASI FM Csisewu, Garut Regency, West Java. The constructivism paradigm is a guideline in a series of studies to describe the behavior of communication actors in information content. The research aims to determine the existence of the convergence of community media and virtual ethnographic elements of information content on social media.  The researcher used a qualitative approach to describe the speech and communication behavior in the virtual space. Theoretically, the research was carried out with the perspective of communication ethnographic theory, media convergence model, participatory communication concept and local wisdom concept. Research data collection techniques are content documentation on social media, interviews, and observations. A series of information on social media such as Instagram, Youtube, Facebook and TikTik were analyzed using a virtual ethnography method The results of the analysis showed that community radio implemented media convergence in rural areas with a global reach. Virtual ethnography contains audio-visual texts, symbols of local wisdom, aspects of development, participation and audience interaction.